To find the equation that represents the additive rule in the table, we can examine the relationship between the values of \(x\) and \(y\).
From the given points in the table:
- When \(x = 25\), \(y = 38\)
- When \(x = 27\), \(y = 40\)
- When \(x = 29\), \(y = 42\)
We can observe that \(y\) is consistently 13 greater than \(x\):
- \(38 = 25 + 13\)
- \(40 = 27 + 13\)
- \(42 = 29 + 13\)
Thus, we can express this relationship in the form of an equation:
\[ y = x + 13 \]
Therefore, the correct response is:
y = x + 13.